Fighting for Justice for Women who Kill Abusive Partners - Harriet Wistrich; Pragna Patel (International Journal for Crime, Justice and Social Democracy)
This article examines the collaborative process involved in campaigning for and representing women appealing murder convictions, highlighting the power of positive collaboration between lawyers, campaigners, frontline experts and the women themselves. Pragna Patel and Harriet Wistrich, who first met while protesting in the early 1990s outside the Royal Courts of Justice in London, have been pivotal figures in this movement. Patel has dedicated four decades to Southall Black Sisters, an organisation advocating for black and minority women. Wistrich co-founded Justice for Women and later specialised in representing women victim-survivors of male violence, challenging discrimination in the criminal justice system.